Increased Intraepidermal Nerve Fiber Degeneration and Impaired Regeneration Relate to Symptoms and Deficits in Parkinson's Disease - Jeziorska, Maria; Atkinson, Andrew; Kass-Iliyya, Lewis; Javed, Saad; Kobylecki, Christopher; Gosal, David; Marshall, Andrew; Silverdale, Monty; Malik, Rayaz A. (Frontiers in Neurology, 2019)
Background: Previous studies have shown cutaneous small fibre pathology in patients with Parkinson’s disease (PD). These studies have focused on nerve degeneration, but recent reports suggest that nerve regeneration may also be important in PD pathology. Objective: To establish the extent of intraepidermal nerve fibre (IENF) degeneration and regeneration and its relationship to clinical and neurological deficits in Parkinson’s disease (PD). Methods: Twenty-three PD patients and 10 age-matched controls underwent skin biopsy and assessment of somatic and autonomic symptoms and deficits. We have assessed Intraepidermal Nerve Fibre Density (IENFD) using standard PGP9.5 staining and GAP-43 to assess Mean Dendritic Axonal Length (MAL) and Intraepidermal Total Nerve Fibre Length (IETNFL). Results: IENFD (p<0.0001), MAL (p<0.0001), IETNFL/Area (p=0.009) and IETNFL/Length (p=0.04) were significantly reduced in patients with PD compared to controls. IENFD correlated significantly with disease duration (p=0.03), cumulative levodopa dose (p=0.02), Unified Parkinson's Disease Rating Scale, Part III (UPDRS-III) (P=0.01), Schwab and England Activities of Daily Living (ADL) (p=0.03), NSP (p=0.03) and 30:15 ratio (p=0.03). IETNFL/Area correlated with the Autonomic Scale for Outcomes in Parkinson's Disease (SCOPA-AUT) (p=0.03) and Diabetic Neuropathy Symptom score (DNS) (p=0.04) and IETNFL/Length correlated with DNS (p=0.03). MAL correlated with SCOPA-AUT (p=0.01), DNS (p=0.02) and DB-HRV (p=0.02). Conclusion: Increased IENF degeneration and impaired regeneration correlates with somatic and autonomic symptoms and deficits in patients with PD.